2009
DOI: 10.1007/s11104-009-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel technique shows different hydrophobic chemical signatures of exotic and indigenous plant soils with similar effects of extracts on indigenous species seedling growth

Abstract: Korth, J. (2010). Novel technique shows different hydrophobic chemical signatures of exotic and indigenous plant soils with similar effects of extracts on indigenous species seedling growth. Plant and Soil: international journal on plant-soil relationships, 326 (1-2), 403-414.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Although the litter of A. mearnsii has been reported to have less sources of hydrophobic substances (Scott, 2000), it still can contain molds, fungi and other agents of decomposition that cause the litter layer to be hydrophobic. Ens et al (2010) reported that A. longifolia leaves possess hydrophobic compounds which causes soil hydrophobicity, which in turn triggers soil compaction, reduced water infiltration and hydraulic conductivity. Also, plant canopy has been reported to influence the intensity and duration of both light and water received by the soils (Kahi et al, 2009), which in turn affect soil moisture and soil temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Although the litter of A. mearnsii has been reported to have less sources of hydrophobic substances (Scott, 2000), it still can contain molds, fungi and other agents of decomposition that cause the litter layer to be hydrophobic. Ens et al (2010) reported that A. longifolia leaves possess hydrophobic compounds which causes soil hydrophobicity, which in turn triggers soil compaction, reduced water infiltration and hydraulic conductivity. Also, plant canopy has been reported to influence the intensity and duration of both light and water received by the soils (Kahi et al, 2009), which in turn affect soil moisture and soil temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several methods have been used to detect allelochemicals in soils, mostly based on the extraction of chemicals from the soil (Inderjit and Nilsen, 2003;Lin et al, 2007;Ens and French, 2008;Ens et al, 2009b;Mohney et al, 2009), but by using organic or inorganic solvents, the non-volatile metabolites and those which do not originate from roots or those which are transformed by soil microbes, may also be extracted. Here, with the assistance of headspace solvent microextraction (HSME) and solid phase microextraction (SPME), we confirmed that live roots introduce phytotoxic substances into the soil; these may last for a long time or may be microbially transformed and subsequently inhibit the germination or the growth of competing plants.…”
Section: Discussionmentioning
confidence: 99%
“…By exuding a wide variety of compounds, roots can control the soil microbial community, interact with herbivores, stimulate beneficial symbioses, affect the chemical and physical properties of the soil, inhibit the growth of competing plant species, and communicate with other species (Bertin et al, 2003;Walker et al, 2003;Bais et al, 2006). While various non-volatile water-soluble allelochemicals, such as metatyrosine, and various carbohydrates and proteins have been described (Bertin et al, 2007), the allelopathic roles of volatiles emitted from the roots have not been as thoroughly explored (Lin et al, 2007;Ens and French, 2008;Ens et al, 2009b). 1,8-cineol is one of the few volatile organic compounds (VOCs) emitted from the roots of of Arabidopsis thaliana, and its root-specific terpene synthase have been characterized (Chen et al, 2004;Steeghs et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roots of plants are known to exploit such patchiness by preferentially growing in soil macropores (Passioura 1991) and several non-mycorrhizal plant species have been found to produce short-lived root clusters which can be effective at extracting phosphorus when its available concentrations are very low (Lambers et al 2006). Variation of properties such as soil pH, moisture, nutrient content, microbial populations, and allelochemical concentrations in time and space and from point to point along a root system is likely to have profound consequences for plant-plant interactions (Blum 2011), and the importance of developing analytical tools that can sensitively measure such variation without disturbance of the soil has received increasing emphasis (Ens et al 2010;Inselsbacher et al 2011;Rudolph et al 2013).…”
Section: Introductionmentioning
confidence: 99%